2001
DOI: 10.1097/00004691-200101000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Seizure Identification

Abstract: Patients with epilepsy may not always be able to identify their seizures. Epilepsy management relies on patient reporting to validate whether seizures occur during treatment. The goal of this study was to assess the frequency of unreported seizures recorded during routine outpatient ambulatory EEG recording. The authors reviewed 552 records from 502 patients who underwent outpatient 16-channel computer-assisted ambulatory EEG monitoring (CAA-EEG). Seizure identification was evaluated by assessing push-button a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…The observation of brief stereotyped recurrent abnormal behaviour in patients at risk of developing epilepsy is considered a tell-tale sign of the condition (Beghi et al ., 2005; Fisher et al ., 2005). However, complex partial seizures—the seizure type for which novel treatments are most needed (Juul-Jensen, 1986; Mattson et al ., 1985; 1996; Semah et al ., 1998)—often present subtly with staring, memory lapses, muscle twitching or impairment in normal function that may go unrecognized by both patients and physicians (Blum et al ., 1996; Tatum et al ., 2001), and can be virtually impossible to detect in animals. Indeed, before diagnosis is confirmed by scalp encephalography (EEG), human complex partial seizures are often first identified through either the patients’ altered state of consciousness or their self-reported internal subjective experience, information not obtainable from animals.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of brief stereotyped recurrent abnormal behaviour in patients at risk of developing epilepsy is considered a tell-tale sign of the condition (Beghi et al ., 2005; Fisher et al ., 2005). However, complex partial seizures—the seizure type for which novel treatments are most needed (Juul-Jensen, 1986; Mattson et al ., 1985; 1996; Semah et al ., 1998)—often present subtly with staring, memory lapses, muscle twitching or impairment in normal function that may go unrecognized by both patients and physicians (Blum et al ., 1996; Tatum et al ., 2001), and can be virtually impossible to detect in animals. Indeed, before diagnosis is confirmed by scalp encephalography (EEG), human complex partial seizures are often first identified through either the patients’ altered state of consciousness or their self-reported internal subjective experience, information not obtainable from animals.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of therapeutic intervention is measured by patient seizure counts. Based on previous studies, it has been noted that patients do not report up to half of their seizures [14–18]. Such underreporting may undermine the everyday care of patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of patient report about their seizures has been studied in the form of diaries or seizure counts mostly during inpatient video-EEG monitoring. Surprisingly, overall, patients do not report 30–50% of their seizures [14–18]. This has obvious consequences for patient care and the accuracy of clinical drug trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] One study also reported its application in adults when under reporting of seizure frequency was suspected, to optimize the treatment. [5] It has also been used to help in identifying patients at low risk of recurrent seizures, among the patients presenting with infrequent seizures prior to drug treatment. [6] It has also been used to quantify paroxysmal discharges in patients with typical absence epilepsies by a limited recording over 8 h.[7]…”
Section: Discussionmentioning
confidence: 99%